Factors influencing health service utilization among the elderly in Insein Township, Yangon Region - Sandar Min Min Hlaing; Naw Clara; Aye Nanda Han (Makara Journal of Health Research, 2020)
Background: With the increasing needs of the aging population and the increasing prevalence of non-communicable diseases, assessment of the equity and accessibility of health care among the elderly has become important.